Current considerations on the teratogens and their effects during pregnancy - Sandra Yiset Calzadilla Lara; Aylén Uriarte Nápoles; Farah María Ricardo Saint Félix; Cecilia Melian Savigñón (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The development reached by teratology as science and the clinical observations made by the scientists,  allowed to establish their principles, represented by a series of factors that determine the capacity of an agent to cause congenital dysfunctions, which are at the moment of great utility and importance in the training of health professional and  rebound in the Infantile Maternal Care Program.  Objective: To describe the teratogen agents associated with the appearance of congenital defects.    Methods: A literatura review was carried out about the teratogen agents and their possible teratogenic effects in the LILACS, SciELO, Clinicalkey databases and Academic Google, as well as in the platform Virtual Library in Health.  Results: The consequences of the exhibition to the teratogen depend, among other things, of the moment in which is the gestation process. There are multiple teratogen agents and some risk factors that frequently concomitan with them, for what should be considered in the primary prevention to diminish alterations and congenital defects for these environmental noxas.  Final considerations: The knowledge of the effects of the agents teratogen allows to value the possible damage to the fetus.